Uji Protein Dan Organoleptik Es Krim Komposisi Kacang Merah Phaseolus Vulgaris Dan Susu Skim Dengan Penambahan Mangga Kuweni Mangifera Odorata - Winarni, Sri (2016)
Ice cream is dairy products through the freezing process. The raw material is kidney bean ice cream, skim milk and mango kweni. Kidney bean contains 23.1 g protein, 59.5 g carbohydrate, 1.7 g fat and higher in fiber. The purpose of this study was to determine levels of protein, organoleptic quality and public acceptability composition of kidney bean ice cream and skim milk with the addition of mango kweni. The method used is experimental research with a completely randomized design (CRD) two factors, the first is composition of kidney beans: skim milk (25%: 75%, 50%: 50%, 75%: 25%, 100%: 0%) and factor two is mango kweni (10 g and 20 g) with two replications. Data were analyzed with descriptive qualitative and quantitative. Results showed the highest protein content of ice cream in the treatment M2K2 (50% skim milk, 50% kidney bean and 20% mango kweni), amounting to 3.0 g. While the low protein content of ice cream, the treatment M2K4 (0% skim milk, kidney bean 100%, and 20% mango kweni), 2.3 g. Ice cream with 100% of kidney bean extract treatment + 0% of skim milk +20% of mango kweni is ice cream that can be accepted by society.